Impact of dielectric constant of solvent on the formation of transition metal-ammine complexes - Manna, Debashree; Lo, Rabindranath; Miriyala, Vijay Madhav; Nachtigallová, Dana; Trávníček, Zdeněk; Hobza, Pavel (Journal of computational chemistry, 2024)
The DFT-level computational investigations into Gibbs free energies (ΔG) demonstrate that as the dielectric constant of the solvent increases, the stabilities of [M(NH3 )n ]2+/3+ (n = 4, 6; M = selected 3d transition metals) complexes decrease. However, there is no observed correlation between the stability of the complex and the solvent donor number. Analysis of the charge transfer and Wiberg bond indices indicates a dative-bond character in all the complexes. The solvent effect assessed through solvation energy is determined by the change in the solvent accessible surface area (SASA) and the change in the charge distribution that occurs during complex formation. It has been observed that the SASA and charge transfer are different in the different coordination numbers, resulting in a variation in the solvent effect on complex stability in different solvents. This ultimately leads to a change between the relative stability of complexes with different coordination numbers while increasing the solvent polarity for a few complexes. Moreover, the findings indicate a direct relationship between ΔΔG (∆Gsolvent -∆Ggas ) and ΔEsolv , which enables the computation of ΔG for the compounds in a particular solvent using only ΔGgas and ΔEsolv . This approach is less computationally expensive.
Keywords: charge transfer; COSMO; dielectric constant; solvation energy; transition metals; ammine complexes; dative bond